PRACTICES OF COLLABORATIVE GOVERNANCE IN ENHANCING CREATIVE ECONOMY IN SUKABUMI CITY: A CASE STUDY OF SUKABUMI CREATIVE HUB (SCH) - Putik Aulia Safitri; Rizki Hegia Sampurna; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The creative economy is a sector that will be strengthened as an economic pillar in the future. In Sukabumi city itself, with limited natural resources, the creative economy is another alternative as an attraction as well as a large economic potential and is one of the priority areas of development. to realise this, the Sukabumi city government formed Sukabumi Creative Hub (SCH) as a committee to accelerate the creative economy in Sukabumi city. this research aims to find out how the governance practices of collaboration between SCH and the sectors of Academia, Government, Business, Community and Media. Community and media. In measuring the governance practices of collaboration, this study uses the theory of Ansell and Gash (2008) which has 4 dimensions namely Starting conditions, Facilitative Leadership, Institutional Design and Collaborative Process. The research method used in this research is leatherative with a case study approach. The results of this study indicate that the collaboration governance run by Sukabumi Creative Hub with stakeholders has fulfilled the criteria of the 4 dimensions of Ansell & Gash (2008) but have not been optimal.